25 years of dust acoustic waves. (25th June 2014) - Merlino, Robert L.
Abstract : The dust acoustic wave (DAW) was first discussed by P. K. Shukla in May of 1989 at the First Capri Workshop on Dusty Plasmas. In the past 25 years, the subsequent publication of the linear and nonlinear properties of the DAW (Rao, N. N., Shukla, P. K. and Yu, M. Y. 1990 Planet. Space Sci. 38, 543) has generated and sustained a large body of theoretical and experimental research that has clarified the physics of collective effects in dusty plasmas. A unique feature of the DAW is that it can be observed (literally) using laser illumination and high-speed videography, revealing details of wave-particle interactions at an unprecedented single particle level. This paper attempts to review some of the contributions and extensions of dust acoustic wave physics, as well as identify recent findings that illustrate the potential importance of this dust wave in the agglomeration of dust particles.